Analysis of the Potential for Wind Power Generation in the Cermin Beach Area as An Energy Reserve - Hutabarat, Purnama Helena T; Yanti, Darma (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
The potential for wind energy in the Pantai Beach Team Park, Deli Serdang Regency, North Sumatra, as an alternative energy for PLTB (Wind Power Plant) is very possible. Looking at the geographical location and average wind speed at this location, this location has the potential to build a PLTB. To get more precise and accurate design results, help from the HOMER application is needed. Where the application used will help to design and determine the PLTB capacity that is capable of carrying the calculated load. In this research, wind power plant (PLTB) planning will be carried out at the research location, namely the tourist area of PT. Serdang Bedagai Cermin Beach. The planning carried out includes technical analysis of PLTB planning which will supply the existing load. The wind speed at the research location was relatively small, namely the largest occurred in December with a speed of 3.18 m/s. while the average wind speed at the research location is 2.63 m/s, the mass flow rate is 133.46 kg/s, the potential power is 2001 watts, the efficiency power is 1600 watts and the system power is 18.9 Watts/m2 where this speed relatively small for the construction of a wind turbine or PLTB. To supply a kWh load of 1,144 kWh/day, a wind turbine with a capacity of 10 kW is needed as many turbines with an output power of 2001 watts per turbine.